Influence of carbon black on the mechanical properties of engineered cementitious composites containing rubber crumb - Chong, Dominic (2015)
The interest in producing a self-sensing engineered cementitious composite (ECC) has been growing. One method that has been proposed to enhance the self-sensing properties of ECC is to include carbon black into the cement matrix. However, the inclusion of carbon black into the cement matrix has produced results that indicate a slightly poorer performance with regards to tensile applications. Other research has indicated that the use of rubber crumb particles and ground granulated blast slag (GGBS) may help the carbon black ECC to perform better in tensile applications. Furthermore, GGBS and rubber crumb are by-products of different industrial processes. The usage of such products contribute to a mix that is less detrimental to the environment. However, the addition of rubber crumb and GGBS may affect other mechanical properties of the ECC. This final year project is designed to investigate the mechanical properties when carbon black, GGBS and rubber crumb are used together to form an ECC. It also aims to determine the viability of using such an ECC in actual construction or repair works in replacement of regular concrete. The 4-point bending flexural test, direct tension test and compressive test will be used to investigate the mechanical properties of the ECC. The results of this report highlight the increase in performance mechanically when GGBS and rubber crumb are added into the cement matrix in conjunction with carbon black particles. It also points out the potential of using this ECC to replace regular concrete.